Investigation on the Levels of Aggression of Physical Education and Sport School Students from Demographic Variables Perspective: Istanbul Ayvansaray University - Cüneyt Seydioğlu; Ihsan Yagci (Journal of Educational Issues, 2024)
The aim of this study is to determine whether the level of aggression of the students of Physical Education and Sports School at Istanbul Ayvansaray University differs according to some demographic variables. For this purpose, 180 students from the Physical Education and Sport School participated voluntarily who got trainings from Istanbul Ayvansaray University’s Coaching Education Department, Sports Management Department, Recreation and Exercise and Sports Sciences Department. Survey data were obtained from the “personal information form” and the “Aggression Scale” developed by Buss-Perry, adapted to Turkish by Madran (2013). SPSS 21 package program was used to analyze the obtained data. In the analysis of the data, T-Test and One Way analysis of variance analysis were used. The difference between the variables was interpreted on the basis of p 0.05 significance level. As a result of the study, although there were significant differences between the aggression levels of the students according to age and sex, the differences between the sections they studied and the level of aggression according to the field they were doing were meaningless. Students with alcohol and cigarette addictions were found to have higher levels of aggression. It was found that the mean score of male students was higher than that of female students.